Prosthetic dreams: "Wow Effect", mechanical paradigm and modular body - prospects on prosthetics - Goffette, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Over the last few decades a number of improvements in prostheses have transformed disability sport. A philosophical, prospective approach reveals three phenomena. Firstly, the public reception of the Paralympic Games has generated what one can call a `Wow Effect`, combining amazement, technological interest and thoughtful states of mind, with both positive and negative effects for the representation of disabled persons. Secondly, the role of prosthetics impels us to perceive many disabled sports as mechanical sports, with different possible patterns of regulation, from prohibition to laissez-faire. Thirdly, the present paper pleads for a sports model that is different from that of able-bodied sports, insisting less on rivalry/hierarchy and more on enjoying new ways of being, new ways of experiencing our relationship with abilities, disabilities, super-abilities and alter-abilities. In fact, disability sport can be viewed as a laboratory for the modular body, which is a topic that concerns all of us.